Ti-based solid solution carbonitrides prepared from Ti-alloy scraps via a hydrogenation-dehydrogenation process and high-energy milling - Jung, Sun-A; Kwon, Hanjung; Roh, Ki-Min; Suh, Chang-Yul; Kim, Wonbaek (Metals and materials international, 2015)
Ti-based solid-solution carbonitrides (Ti,Al,V)(CN) and (Ti,Al,Mo,V)(CN), were synthesized successfully using Ti-6Al-4V (Ti-64) and Ti-8Al-1Mo-1V (Ti-811) alloy scraps via hydrogenation-dehydrogenation and highenergy milling processes. A single phase of (Ti,Al,V)(CN) could be readily synthesized by the high-energy milling of Ti-64 alloy with graphite in a nitrogen atmosphere regardless of the carbon content. On the other hand, for the Ti-811 alloy, metallic Mo and various Mo-less carbides, in this case Ti 2 AlC, Ti 3 AlC 2 , and Ti 3 AlC, were also formed in addition to (Ti,Al,Mo,V)(CN) due to the low nitrogen affinity of Mo. The solid-solution carbonitrides consolidated by spark plasma sintering revealed excellent mechanical properties (HV: 19.1-20.6 GPa, KIC: 5.2-6.4 MPa·m 1/2 ) due to the alloying effect of Al, Mo, and V in Ti(CN). These values are superior to those of typical Ti(CN)–based ceramic composites (H V : 16-20 GPa, K IC : 3.2-5.5 MPa·m 1/2 ). We believe that the suggested method would be a valuable option for the production of Ti-based solid-solution carbonitrides with decent mechanical properties economically.